Determinants of procreative attitudes of Polish women over the years - Renata Bajcarczyk; Renata Florek (Studia Medyczne, 2018)
In 1999, for the first time in Poland, negative natural population growth was recorded, which caused media-political discussions on the development of the population of Poland. The phenomenon of population decline was a surprise, because the Central Statistical Office forecasts were too optimistic and in 1998 they predicted an increase in the population of Poland to 40 million in 2010. In discussions, apart from the debates on the catastrophic demographic situation in Poland and calls for an immediate increase in fertility, there are arguments about maintaining appropriate proportions between groups of people of working, pre-productive and post-working age, as well as appropriate protection of living conditions, education, work and health protection for new generations. The subject of the analysis is shaping the population policy after World War II, its impact on the population size and also the impact of the country’s economic situation and socio-ethical changes on demographic changes.